HUBUNGAN STRES AKADEMIK DAN KONSUMSI KAFEIN DENGAN KUALITAS TIDUR PADA REMAJA DI MAN 11 JAKARTA - Nida Julia Nafi'awani (2023)
Adolescence is a period of transition from childhood to adulthood where adolescents are dominated by students, and they are often suffering from stress caused by their academics. Teenagers who experience academic stress will likely seek and find ways to reduce the stress, and one of its way is by consuming caffeine. If teenagers consume caffeine excessively due to stress, it can cause health problem, one of the problem is it will affect their quality of sleep. This study aims to determine the relationship between academic stress and caffeine consumption with sleep quality in adolescents at MAN 11 Jakarta. In this study used cross sectional approach, the amount of sample for this study was 215 adolescents and the sampling was carried out using a stratified random sampling technique. The data was collected using ESSA (Educational Stress Scale for Adolescents), Caffeine Intake assessment, and PSQI (The Pittsburgh Sleep Quality Index) instrument. The result of this study indicated that there is a significant correlation between academic stress and sleep quality in adolescents with a significance value 0,000 (p≤0.05) and there is no significant correlation between caffeine consumption and sleep quality with a significance value 0,072 (p>0,05). This study can provide information to adolescents about academic stress, caffeine consumption, and sleep quality so that with this information adolecents can control academic stress and maintain caffeine consumption within normal limits so they can achieve a good quality of sleep.